Empirical Study of Family Conflicts as a Factor of Emotional Burnout of a Woman - Biletska, Iryna O.; Kotlova, Liudmyla O.; Kotlovyi, Serhii A.; Beheza, Liudmyla Ye.; Kulzhabayeva, Lyazzat S. (Journal of Intellectual Disability - Diagnosis and Treatment, 2020)
Objective: Conflict issues have always been relevant to any society, but in Ukraine, at all stages of its development, conflicts had not just a noticeable place, but also influenced its history. Background: Conflicts, of course, adversely affect these processes, because a woman spends most of her life in the family and, of course, the climate inside the family affects the emotional state of all its members. Method: To study the relationship between the level of conflict in the family and the emotional burnout of a woman, we used the following research methods: empirical – methodologies of Y. Aleshina, L. Hoffmann, E. Dubovskaya "The nature of the interaction of the matrimony in conflict situations” and V. Boiko “Diagnostics of emotional burnout”, statistical – Pearson’s linear correlation coefficient. Results: The study involved 80 participants. The study also determined the relationship between the evaluation of the work-life balance and organizational parameters. As a result of the study, we determined that the syndrome most characteristic of women is exhaustion, at the average level – stress, at a low level, is a resistance. Conclusion: The study suggests that in families with a high level of conflict, there is emotional exhaustion in women.